Colon/Colon (C18.9) - Long-term results after endoscopic dilatation of post-operative colo-colonic anastomotic stenoses. Our experience in 42 patients - Tomasello, G.; Palumbo, V.D.; Damiani, et al., P. (European Journal of Oncology and Environmental Health, 2013)
Summary. Aim: The aim of this study is to evaluate long-term complications and patients’ quality of life after  the endoscopic treatment of benign anastomotic colo-colonic strictures. Patients and Methods: From January 2000 to November 2008, 42 patients who had undergone surgery for colorectal cancer were endoscopically treated for a postoperative symptomatic stricture. The dilation were performed using a 20-30 mm pneumatic dilator. The clinical results were classified in relation to the abdominal symptomatology reported by the patients, and were evaluated in the short-term (one week) and long-term (mean follow-up: 36 months) period. Results: 15 patients underwent a total of 22 dilating sessions; 9 patients had a single dilating session; 18 patients underwent 5 dilating sessions. Three bowel perforations at the site of dilation, 1 septic complication and a transient mucosal bleeding were registered. Immediate symptomatic relief was achieved in all the cases; the symptoms caused by the strictures disappeared after the first session. Normal defecation was immediately restored after the treatment. Satisfactory good long-term clinical results were achieved in thirty-seven patients (88%). Conclusions: This study confirms the assumption that dilation with balloon may be considered the first-line therapeutic approach safe and effective for symptomatic benign anastomotic strictures after colorectal resection surgery for adenocarcinoma. The treatment of benign anastomotic strictures by standard endoscopic dilation is an effective contribution against stricture-related gastrointestinal symptoms. The standard criterion used to define successful anastomoses dilations (10-13 mm in diameter) is sufficient for an optimal result. Risultati a lungo termine dopo dilatazione endoscopica di stenosi post-operatorie di anastomosi colon-coliche. nostra esperienza in 42 pazientiRiassunto. Obiettivo: L’obiettivo di questo studio è valutare le complicanze a lungo termine e la qualità di vita dei pazienti dopo trattamento endoscopico delle stenosi benigne in sede di anastomosi colon-colica. Pazienti e Metodi: Dal gennaio 2000 al novembre 2008, 42 pazienti che avevano subito un intervento chirurgico per tumore del colon-retto sono stati trattati endoscopicamente per stenosi sintomatica post-operatoria. Le dilatazioni sono state eseguite mediante dilatatore pneumatico di 20-30 mm. I risultati clinici sono stati classificati in relazione alla sintomatologia addominale riportata, e sono stati valutati a breve (una settimana) e lungo termine (follow-up medio: 36 mesi). Risultati: 15 pazienti sono stati sottoposti a 22 sessioni di dilatazione, 9 pazienti ad una singola sessione di dilatazione, 18 pazienti a 5. Sono state registrate solo 3 perforecurrazioni intestinali nel sito di dilatazione, 1 complicazione settica e un sanguinamento transitorio della mucosa. Un immediato sollievo sintomatologico è stato raggiunto in tutti i casi; i sintomi causati dalla stenosi sono scomparsi dopo la prima sessione. Subito dopo il trattamento si è ristabilita una normale defecazione. Risultati clinici sufficientemente buoni a lungo termine sono stati raggiunti in 37 pazienti (88%). Conclusioni: Questo studio conferma che la dilatazione con pallone pneumatico può essere considerata la prima linea di approccio terapeutico sicuro ed efficace per le stenosi anastomotiche benigne sintomatiche dopo intervento chirurgico di resezione del colon-retto per adenocarcinoma. Il trattamento endoscopico delle stenosi benigne anastomotiche è uno strumento efficace contro i sintomi ostruttivi dovuti alle stenosi. Il criterio standard utilizzato per definire il successo della dilatazione (10-13 mm di diametro) è sufficiente per un risultato ottimale.